Bladder Endometriosis: A Great Masquerader - Rana, Parveen; Hooda, Sunaina; Agarwal, Ruchi; Parul; Gathwal, Monika; Rohilla, Vishal; Saluja, Swaran Kaur (Annals of Pathology and Laboratory Medicine, 2025)
Endometriosis is a chronic condition presenting with the presence of endometrium outside the uterus. Case 1: A 29-year-old woman presented with abdominal pain and painful urination for 15 days, beginning after her menstrual cycle. She had a history of frequent urination, recurrent urinary tract infections, hematuria, and two uneventful cesarean sections. Ultrasound revealed a lobulated soft tissue lesion in the posterior bladder wall. Microscopy revealed endometrial glands and hemosiderin-laden macrophages. Immunohistochemistry (IHC) confirmed bladder endometriosis with positive estrogen and progesterone receptors (ER/PR) and CD10-positive stromal cells. Case 2: A 33-year-old woman with menorrhagia, dysmenorrhea, and burning urination underwent surgery for a fibroid and ovarian cyst. During surgery, a 6.5 cm firm mass adhered to the bladder and uterus was found. Histopathology confirmed bladder endometriosis with ER-positive glands. The diagnosis of bladder endometriosis is aided by imaging techniques along with histopathology and IHC. This comprehensive approach helps differentiate bladder endometriosis from malignancies or other gynecological conditions, thus reducing the risk of misdiagnosis. Early and precise diagnosis facilitates targeted treatment, improving patient outcomes and preventing unnecessary interventions.